Bottleneck Identification through Simulation Modelling: A Case of Solid Tire Manufacturing Sector - EDIRISINGHE, Edirisinghe Arachchige Dona Dilesha Divyanjali; KARUNARATHNE, Edirisinghe Arachchige Chaminda Prasanna (Management Dynamics in the Knowledge Economy, 2023)
Businesses are constantly making productivity improvements to survive in the highly competitive marketplace. Bottlenecks have been identified as one of the main factors limiting the system performance of manufacturing firms. Thus, identifying bottlenecks in the production process is extremely important to increase productivity. Considering its importance, this case study was designed to identify causes for not meeting the tire target and determine the implications of bottlenecks in the tire manufacturing process. For this purpose, simulation analysis was carried out for the solid resilience tire-building process. Through the investigation, the cushion layer-building process was identified as the bottleneck. To validate the identified limitation, Line balancing and Pareto analysis were conducted. Analysis results confirmed the presence of a bottleneck in the cushion layer-building process. Further, to identify the root causes for not reaching the maximum tire target, Cause-and-Effect analysis and 5WHY analysis were adopted. The study revealed that inadequately maintained outdated machines and frequent power failures are the leading causes of not meeting the maximum production. By answering these issues, the target production can be increased, and the results showed the opportunity to increase the efficiency of the manufacturing process by more than 95%.